End-Group Evaluation of HEMA Initiated Poly(ε-caprolactone) Macromonomers via Enzymatic Ring-Opening Polymerization - N. Ugur Kaya; Y. Avcibasi Guvenilir (International Journal of Polymer Science)
Poly(ε-caprolactone) (PCL) macromonomers comprising acrylate end-functionality were synthesized via enzymatic ring-opening polymerization (eROP) by utilizing commercially available Candida antarctica Lipase B (CALB), Novozyme-435. 2-Hydroxyethyl methacrylate (HEMA) was purposed to be the nucleophilic initiator in eROP. The side reactions generated due to the cleavage of ester bonds in HEMA and the growing polymer chains were investigated through altering polymerization period, initiator concentration, temperature, and enzyme concentration. 1H NMR evaluations showed that minimum quantities of side reactions were in lower temperatures, initiator concentration, enzyme concentration, and lower monomer conversions. Gel permeation chromatography (GPC) results revealed that lower polydispersity along with number-average molecular weight of end-functionalized PCL macromonomers was obtained depending on higher initiator/monomer ratios, lower temperature (60°C), enzyme concentration (100 mg), and/or polymerization time (2 h). Furthermore, 0.1 HEMA/ε-caprolactone (CL) ratio had higher molecular weight than 0.5 HEMA/CL ratio, while keeping a close value of methacrylate transfer, total methacrylate end-groups, and lower polyester transfer.